Isolation and characterization of glycosaminoglycans in human plasma. - Staprans, I (1985)
We have described methodology for the isolation and quantitation of glycosaminoglycans present in human plasma. Plasma glycosaminoglycans can be quantitatively adsorbed on a DEAE-Sephacel ion exchanger and eluted with a salt gradient as two groups: a low-charge fraction and a high-charge fraction. The low-charge fraction consists of chondroitin sulfate with a low sulfate content and the high-charge fraction consists of heparan sulfate, chondroitin sulfate, and keratan sulfate (type I). We have determined the plasma concentration of each of these glycosaminoglycans in six normal human subjects. We have established that none of the glycosaminoglycans in plasma are covalently linked to plasma proteins. All are isolated as complexes with plasma proteins in noncovalent linkages. The glycosaminoglycans in the low-charge fraction are bound with high affinity to a single plasma glycoprotein by a lectin-type bond that can be disrupted by a simple glycoside. The high-charge fraction contains three major proteins and several minor proteins associated with the glycosaminoglycans by both lectin-type and ionic bonding. The plasma proteins associated with glycosaminoglycans represent less than 0.5% of the total plasma proteins. Little is known about the physiologic role of the plasma glycosaminoglycans as components of metabolic processes. Because glycosaminoglycans have been implicated in lipid metabolism and atherosclerosis, we tested all of these compounds, isolated in free form, on the in vitro hydrolysis of triglycerides by lipoprotein lipase. Plasma heparan sulfate stimulated the rate of this reaction severalfold. All other plasma glycosaminoglycans were inactive. Thus, plasma heparan sulfate may play an important role in plasma lipoprotein metabolism.